Green entrepreneurial intentions among university students in Chile: use of PLS-SEM - Cabana-Villca, Ricardo (2024)
The current study evaluated factors that explain green entrepreneurship intention (GEI) among 407 university students in Chile, who were presented with an online questionnaire. Thirty-nine questions evaluated their GEI, and the data was analysed using multivariate techniques. Results showed thatconcept development support (CDS), business development support (BDS) and academic training support (ATS) had a positive effect on institutional support (IS). Country support (CS) had a positive effect on self-efficacy (SE). IS did not have a positive effect on SE. Finally, SE had a positive effect on GEI. The model explained 25.3% of GEI. Bootstrapping led support to these results. The effects of CDS, BDS, ATS, CS and SE were positive and significant. Recognizing which factors have a significant effect can be useful to devise university programs aiming to enhance GEI among university students. The results of this paper may provide useful indications about future entrepreneurship and possibly suggest ways in which students’ participation in private companies may create successful green products and services.